Identifikasi Senyawa Metabolit Sekunder Ekstrak Metanol Daun Pletekan (Reullia tuberosa L.) - Nur Rafida Akub; Nurhayati Bialangi; Weny J.A Musa; Yuszda K. Salimi; Wiwin Rewini Kunusa; Ahmad Kadir Kilo (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
Indonesia is renowned for its abundant and diserve natural resources, including various plants. Many medicinal plants are traditionally utilized due to their therapeutic benefits. The utilization of minnieroot leaves as a traditional medicine shuld be supported by comprehensive studies to identify the active compounds, thereby omproving their quality, safety and afficacy. Secondary metabolites in minnieroot, particularly in the leaves, contain polyphenolic compounds, while the roots are known to contain flavonoids. This study aims to identify secondary metabolite compounds in minnieroot (Reullia tuberosa L.) leafs methanol extract. The study utilized methanol as a solvent for the extract solution became colorless, resulting in a extract yield of 8,02% of the leaf’s weight. The qualitative test confirmed the presence of secondary matebolites, specifically flavonoids and tannin in the methanol extract of minnieroot leaves. The final result from column chromatography separation shows that crystals are formed in the sixth vial. The crystals areb brownish blackn in color and weigh 0, 1235 g.